A shield synchronous grouting material based on waste ceramic sand and a preparation method thereof

CN122771697APending Publication Date: 2026-09-18CHONGQING JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133374.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0007]本发明的目的是为了克服现有盾构同步注浆材料在富水动水条件下易被冲刷稀释、硬化浆体体积收缩显著、天然河砂资源过度消耗以及现有抗水分散方案组分复杂或严重牺牲流动性等缺陷,从而提供一种基于废弃陶瓷砂的盾构同步注浆材料及其制备方法

Benefits of technology

[0023] In the above technical solution, the shield tunneling synchronous grouting material based on waste ceramic sand of the present invention uses waste ceramic sand of equal mass to replace river sand as fine aggregate. The micropores inside the ceramic sand can fill the gaps between the aggregates, optimize the transition zone between the aggregates and cement stone, and promote the large-scale generation of CSH gel, thereby reducing the dual shrinkage of hardened grout drying and penetration from the source. The low-doped HEMC forms a three-dimensional polymer network structure that encapsulates the grout particles, which can resist the erosion of flowing water without the need for compounding multiple additives. The grout retention rate and 28-day water and land strength are significantly improved. The two work together to offset the fluidity loss caused by HEMC. At the same time, it consumes a large amount of waste ceramic construction waste, reduces the mining of natural river sand, and significantly reduces the overall cost of grouting raw materials. It has multiple material advantages, including mechanical properties, resistance to flowing water, low shrinkage, and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122771697A_ABST
    Figure CN122771697A_ABST
Patent Text Reader

Abstract

This invention relates to the field of building materials and solid waste utilization technology, and in particular to a shield tunneling synchronous grouting material based on waste ceramic sand and its preparation method. The shield tunneling synchronous grouting material comprises cementitious materials, fine aggregates, bentonite, water, and a flocculant. The cementitious materials include cement and fly ash; the fine aggregates are composed of river sand and waste ceramic sand, with the waste ceramic sand accounting for 10-30% of the total mass of the fine aggregates; the flocculant is hydroxyethyl methyl cellulose (HEMC), with the amount of HEMC being 0.25-0.6% of the total mass of the cementitious materials. This grouting material uses waste ceramic sand in equal mass to replace river sand as fine aggregate, promoting C-S-H gel formation and reducing shrinkage. Simultaneously, HEMC acts as a flocculant, with its hydrophilic groups forming hydrogen bonds with water molecules, constructing a three-dimensional fibrous cross-linked network within the grout, binding solid particles, inhibiting water erosion and dilution of particles, and improving the grout retention rate in dynamic water environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials and solid waste utilization technology, and in particular to a shield tunneling synchronous grouting material based on waste ceramic sand and its preparation method. Background Technology

[0002] Synchronous grouting in shield tunnels is a core construction procedure for filling the gaps between tunnel segments and surrounding rock, controlling ground settlement, and resisting groundwater seepage. This is especially crucial for tunnels crossing rivers and lakes, where high water pressure, high flow velocities, and well-developed rock fissures are prevalent. The performance of the grouting material directly impacts the long-term safety and service life of the tunnel lining structure. With the rapid development of urban rail transit and river-crossing tunnel construction in my country, the application of shield tunneling is becoming increasingly widespread, leading to continuously rising performance requirements for synchronous grouting materials.

[0003] However, existing ordinary cement-based grouting materials have revealed several problems in practical engineering applications. First, the bonding force between grout particles is insufficient, making them easily diluted by water flow in dynamic water environments. This leads to significant grout loss, reduced grouting filling rate, and a low ratio of compressive strength between land and water, making it difficult to achieve sufficient early and final strength under underwater curing conditions. Existing improvement schemes often employ multi-component compound anti-dispersion systems of silica fume, hydroxyethyl cellulose (HEC), and polyacrylamide (PAM), which suffer from complex components and high preparation costs. Furthermore, PAM significantly degrades the pumping flow performance of the grout. Second, existing grouting materials exhibit significant drying shrinkage and seepage shrinkage during the later stages of hardening, easily forming through-seepage channels behind the lining, greatly increasing the risk of tunnel leakage. Especially in fractured rock masses, water in the grout easily seeps out along the fractures under grouting pressure, leading to exacerbated volume shrinkage. Current research lacks a systematic consideration of these issues.

[0004] Meanwhile, the proportion of fine aggregate in synchronous grouting formulations generally exceeds 40%, resulting in a massive consumption of natural river sand. Affected by resource controls and river mining bans, the supply of natural sand is tight, and its cost continues to rise. China generates a huge amount of construction waste annually, including a considerable amount of waste ceramic bricks and tiles, most of which are currently disposed of through landfill, leading to significant land occupation and water pollution problems. Processing waste ceramics into recycled fine aggregate to replace some of the natural river sand could simultaneously alleviate the dual challenges of sand and gravel resource shortages and ceramic solid waste disposal. However, the compatibility of this type of aggregate in shield tunnel synchronous grouting, as well as its matching mechanism with functional admixtures, has not yet been systematically studied.

[0005] Hydroxyethyl methyl cellulose (HEMC) is a non-ionic cellulose ether. While existing research on slurry shield grouting has introduced this material to improve the water resistance of the grout, most technical solutions require the combination of multiple components such as nano-adjuvants and organic flocculants. Furthermore, the aggregates used in the aforementioned studies are all natural river sand, and there is no research on the combination of HEMC and recycled aggregates for synchronous grouting. Especially for cross-river shield tunnels, the maximum water pressure at the arch can reach 0.7 MPa, and the thickness of the bedrock overburden layer in the underwater section varies greatly with the development of rock joints and fissures. The risk of slurry dispersion and fissure leakage under high-pressure dynamic water conditions is much higher than in conventional shield engineering, placing more stringent requirements on the water dispersion resistance, dynamic water erosion resistance, and shrinkage resistance of the grouting materials.

[0006] In summary, there is an urgent need to develop new materials for synchronous grouting of shield tunnels that can simultaneously realize the resource utilization of ceramic solid waste, resist erosion by dynamic water, and have low volume shrinkage, so as to make up for the shortcomings of the comprehensive performance of existing technologies and provide supporting filling materials for shield tunneling projects with high water pressure fractures across rivers. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing shield tunneling synchronous grouting materials, such as easy scouring and dilution under water-rich and dynamic conditions, significant volume shrinkage of hardened grout, excessive consumption of natural river sand resources, and complex composition or severe loss of fluidity in existing anti-water dispersion schemes. Therefore, this invention provides a shield tunneling synchronous grouting material based on waste ceramic sand and its preparation method. The grouting material of this invention uses waste ceramic sand as a fine aggregate, replacing river sand by the same mass. Ceramic particles fill the gaps between aggregates, optimize the interface transition zone, promote CSH gel formation, and significantly reduce drying and penetration shrinkage. Simultaneously, hydroxyethyl methyl cellulose (HEMC) accounting for 0.25~0.6% of the total mass of the cementitious material is used as a flocculant. The hydrophilic groups on its molecular chain form hydrogen bonds with water molecules, constructing a three-dimensional fibrous cross-linked network inside the grout, binding solid particles, inhibiting water scouring and dilution of particles, improving grout retention rate under dynamic water conditions, and balancing fluidity and underwater strength without the need for multiple modifying additives. Ceramic sand and HEMC form a synergistic effect system, with three types of strata-layered formulas. The slurry has low turbidity and excellent 28-day water-land strength ratio. It can efficiently dispose of ceramic construction waste. The raw materials are readily available, and the preparation process is compatible with existing shield tunneling mixing and pumping equipment. It has advantages in engineering performance, solid waste utilization and construction.

[0008] To achieve the above objectives, in a first aspect, the present invention provides a shield tunneling synchronous grouting material based on waste ceramic sand, wherein the shield tunneling synchronous grouting material comprises cementitious materials, fine aggregates, bentonite, water, and flocculants; wherein... The cementitious material includes cement and fly ash; The fine aggregate is composed of river sand and waste ceramic sand, with the waste ceramic sand accounting for 10-30% of the total mass of the fine aggregate. The flocculant is hydroxyethyl methyl cellulose, and the amount of hydroxyethyl methyl cellulose is 0.25~0.6% of the total mass of the cementitious material.

[0009] Preferably, the cement is PO42.5 ordinary Portland cement with a specific surface area of ​​350~360 m². 2 / kg, density 3~3.1g / cm³ 3 Initial setting time: 220-250 min; final setting time: 280-300 min; 3-day compressive strength: 24-30 MPa; 28-day compressive strength: 48-52 MPa.

[0010] Preferably, the fly ash is Grade I fly ash, with a SiO2 content of 44-46% and an Al2O3 content of 35-38%.

[0011] Preferably, the bentonite is sodium-based bentonite.

[0012] Preferably, the particle size of the river sand is 0.1~1mm.

[0013] Preferably, the particle size of the waste ceramic sand is 0.1~1mm.

[0014] Preferably, the hydroxyethyl methyl cellulose has a viscosity of 80,000 to 120,000 mPa·s and a purity of ≥98%.

[0015] Preferably, the shield tunneling synchronous grouting material is composed of the following components by weight: 500-600 parts cementitious material, 640-680 parts fine aggregate, 50-60 parts bentonite, 330-360 parts water and 1.25-3.6 parts flocculant.

[0016] Secondly, the present invention provides a method for preparing a shield tunneling synchronous grouting material as described herein, the method comprising the following steps: 1) Mix bentonite with water and let it stand to expand, thus obtaining bentonite slurry; 2) Mix cement, fly ash, river sand, and waste ceramic sand to obtain a dry mix; 3) Add the bentonite slurry from step 1) to the dry mix from step 2) and mix. 4) Add hydroxyethyl methyl cellulose, dissolve and disperse to obtain the shield tunnel synchronous grouting material.

[0017] Preferably, in step 1), the mixing conditions include: a stirring rate of 40-80 rpm and a time of 2-3 min.

[0018] Preferably, in step 1), the static puffing time is 12~36h.

[0019] Preferably, in step 2), the mixing conditions include: a stirring rate of 50-100 rpm and a time of 3-5 min.

[0020] Preferably, in step 3), the mixing conditions include: a stirring rate of 60~120 rpm and a time of 3~5 min.

[0021] Preferably, in step 4), the conditions for dissolution and dispersion include: a stirring rate of 60~120 rpm and a time of 2~3 min.

[0022] Thirdly, the present invention provides an application of the shield synchronous grouting material as described in the present invention in the synchronous grouting project of the cross-river shield tunnel.

[0023] In the above technical solution, the shield tunneling synchronous grouting material based on waste ceramic sand of the present invention uses waste ceramic sand of equal mass to replace river sand as fine aggregate. The micropores inside the ceramic sand can fill the gaps between the aggregates, optimize the transition zone between the aggregates and cement stone, and promote the large-scale generation of CSH gel, thereby reducing the dual shrinkage of hardened grout drying and penetration from the source. The low-doped HEMC forms a three-dimensional polymer network structure that encapsulates the grout particles, which can resist the erosion of flowing water without the need for compounding multiple additives. The grout retention rate and 28-day water and land strength are significantly improved. The two work together to offset the fluidity loss caused by HEMC. At the same time, it consumes a large amount of waste ceramic construction waste, reduces the mining of natural river sand, and significantly reduces the overall cost of grouting raw materials. It has multiple material advantages, including mechanical properties, resistance to flowing water, low shrinkage, and environmental friendliness.

[0024] Furthermore, this invention employs a room-temperature, stepwise mixing process, requiring only two core steps: dry material premixing and water addition mixing. Bentonite undergoes only conventional pre-expansion treatment, and HEMC is added in the final step. This avoids premature swelling and clumping due to water absorption during prolonged dry mixing with other powders, ensuring full dissolution and uniform dispersion in the liquid phase, thereby maximizing its flocculation and water-retention functions. The entire process requires no heating or pressurization, involves no complex chemical modification steps, is fully compatible with existing shield tunneling synchronous grouting on-site mixing systems, requires no additional special equipment, and is simple to operate with controllable costs.

[0025] The shield tunneling synchronous grouting material of this invention is specifically adapted to the complex working conditions of cross-river tunnels, such as high water pressure and crack development, effectively reducing annular grout loss and late-stage seepage defects in the lining; all indicators fully comply with the T / CECS 563-2018 specification, can stably control ground settlement, extend the service life of tunnel lining, and the solid waste resource utilization scheme is in line with the green construction policy of underground engineering, and has the value of wide-ranging promotion and application.

[0026] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description

[0027] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 (a) is a diagram showing the water dispersion resistance test effect of the shield synchronous grouting material prepared in Comparative Example 1; (b) is a diagram showing the water dispersion resistance test effect of the shield synchronous grouting material prepared in Example 1; (c) is a diagram showing the water dispersion resistance test effect of the shield synchronous grouting material prepared in Comparative Example 3. Figure 2 (a)-(b) are the water dispersion resistance test results of the shield tunnel synchronous grouting materials prepared in Comparative Examples 4-5, respectively; (c)-(e) are the water dispersion resistance test results of the shield tunnel synchronous grouting materials prepared in Examples 2-4, respectively. Figure 3 (a) shows the change in the permeability and loss rate of the shield synchronous grouting material prepared in Example 1 and the shield synchronous grouting material prepared in Comparative Example 7 under the condition of intact sandstone (0.3MPa) over time; (b) shows the change in the permeability and loss rate of the shield synchronous grouting material prepared in Example 1 and the shield synchronous grouting material prepared in Comparative Example 7 under the condition of intact mudstone (0.3MPa) over time. Figure 4 (a) shows the change in permeability and loss rate over time of the shield synchronous grouting material prepared in Example 1 and the shield synchronous grouting material prepared in Comparative Example 7 under the condition of fractured sandstone (0.3 MPa); (b) shows the change in permeability and loss rate over time of the shield synchronous grouting material prepared in Example 1 and the shield synchronous grouting material prepared in Comparative Example 7 under the condition of fractured mudstone (0.3 MPa). Figure 5 (a) is a scanning electron microscope (SEM) image of the shield synchronous grouting material prepared in Comparative Example 1; (b) is a SEM image of the shield synchronous grouting material prepared in Example 1. Figure 6 (a) is the X-ray energy dispersive spectroscopy (EDS) diagram of the shield synchronous grouting material prepared in Comparative Example 1; (b) is the EDS diagram of the shield synchronous grouting material prepared in Example 1. Detailed Implementation

[0028] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0029] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0030] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0031] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0032] In a first aspect, the present invention provides a shield tunneling synchronous grouting material based on waste ceramic sand, wherein the shield tunneling synchronous grouting material comprises cementitious materials, fine aggregates, bentonite, water, and flocculants; wherein... The cementitious material includes cement and fly ash; The fine aggregate is composed of river sand and waste ceramic sand, with the waste ceramic sand accounting for 10-30% of the total mass of the fine aggregate. Natural river sand is subject to river channel mining bans, is scarce, and has rising procurement costs year by year. There is a huge stock of solid waste such as waste ceramic bricks and ceramic fragments. Traditional landfilling occupies land and pollutes water and soil. Using ceramic sand to replace river sand can realize the resource utilization of solid waste and reduce raw material costs. At the same time, waste ceramic sand and HEMC form a synergistic system to offset the fluidity loss caused by cellulose ether, taking into account both pumping performance and underwater stability.

[0033] The flocculant is hydroxyethyl methyl cellulose (HEMC), and the amount of HEMC is 0.25-0.6% of the total mass of the gelling material. HEMC is a non-ionic cellulose ether with a molecular chain rich in hydroxyl and ether hydrophilic groups, which can form hydrogen bonds with water molecules to construct a three-dimensional fiber network. It does not require the addition of multiple additives, and the system is simple.

[0034] This invention relates to a shield tunneling synchronous grouting material based on waste ceramic sand. Waste ceramic sand is used as a fine aggregate to replace river sand of equal mass. The micropores within the ceramic sand fill the gaps between the aggregates, optimizing the transition zone between the aggregates and cement paste, and promoting the formation of large amounts of CSH gel. This fundamentally reduces the dual shrinkage caused by drying and penetration of the hardened grout. Low-doping HEMC forms a three-dimensional polymer network structure that encapsulates the grout particles, resisting water erosion without the need for multiple additives. Grout retention rate and 28-day water-land strength are significantly improved. Both components synergistically offset the fluidity loss caused by HEMC. Simultaneously, it significantly utilizes waste ceramic construction waste, reduces the mining of natural river sand, and substantially lowers the overall cost of grouting raw materials. It possesses multiple material advantages, including mechanical properties, resistance to water erosion, low shrinkage, and environmental friendliness.

[0035] In this invention, the cement is PO42.5 ordinary Portland cement, a common cementitious material for synchronous grouting in tunnel boring machines, with a moderate hydration rate and balanced early and late strength; its specific surface area is 350~360 m². 2 / kg, density 3~3.1g / cm³ 3 The initial setting time is 220-250 min, the final setting time is 280-300 min, the 3-day compressive strength is 24-30 MPa, and the 28-day compressive strength is 48-52 MPa. The specific surface area, strength, and setting range are limited to match the synergistic hydration requirements of fly ash and ceramic sand in this system, and sufficient window space is reserved for shield tail filling operations to prevent premature setting.

[0036] In this invention, the fly ash is Grade I fly ash, with a SiO2 content of 44-46% and an Al2O3 content of 35-38%. The silicon and aluminum oxides can undergo secondary hydration with Ca(OH)2 in cement hydration, filling the microscopic pores of the slurry; Grade II and lower fly ash have insufficient fineness and contain more impurities, which will increase bleeding and reduce the strength of the cementitious stone.

[0037] In this invention, the bentonite is sodium-based bentonite. Sodium-based bentonite has a high montmorillonite content and excellent water absorption and swelling properties, serving as a suspension stabilizer to prevent aggregate sedimentation and stratification.

[0038] In this invention, the particle size of both the river sand and the waste ceramic sand is 0.1~1mm. The aggregate gradation is continuous, the packing density is high, reducing the internal voids of the slurry, reducing volume shrinkage, and ensuring smooth pumping of the slurry without clogging the pipes.

[0039] In this invention, the hydroxyethyl methyl cellulose has a viscosity of 80,000~120,000 mPa·s and a purity of ≥98%. High-purity long-chain HEMC stably constructs a three-dimensional fiber skeleton, locking in cement and ceramic particles; the viscosity range balances anti-dispersion properties and pumpability.

[0040] In this invention, the shield tunnel synchronous grouting material is composed of the following components by weight: 500-600 parts of cementitious material, 640-680 parts of fine aggregate, 50-60 parts of bentonite, 330-360 parts of water and 1.25-3.6 parts of flocculant.

[0041] Secondly, the present invention provides a method for preparing a shield tunneling synchronous grouting material as described herein, the method comprising the following steps: 1) Mix bentonite with water and let it stand to expand, thus obtaining bentonite slurry; 2) Mix cement, fly ash, river sand, and waste ceramic sand to obtain a dry mix; 3) Add the bentonite slurry from step 1) to the dry mix from step 2) and mix. 4) Add hydroxyethyl methyl cellulose, dissolve and disperse to obtain the shield tunnel synchronous grouting material.

[0042] This invention employs a room-temperature, stepwise mixing process, requiring only two core steps: dry material premixing and water addition. Bentonite undergoes only conventional pre-expansion treatment, and HEMC is added in the final step. This avoids premature swelling and clumping due to water absorption during prolonged dry mixing with other powders, ensuring full dissolution and uniform dispersion in the liquid phase, thereby maximizing its flocculation and water-retention functions. The entire process requires no heating or pressurization, involves no complex chemical modification steps, is fully compatible with existing shield tunneling synchronous grouting on-site mixing systems, requires no additional special equipment, and is simple to operate with controllable costs.

[0043] In step 1) of this invention, in order to make the bentonite uniformly dispersed without lumps and to provide a basis for full expansion, the mixing conditions include: a stirring rate of 40~80 rpm and a time of 2~3 min.

[0044] In step 1) of this invention, the static swelling time is 12-36 hours. This allows the bentonite to fully absorb water and swell, forming a stable suspended substrate and reducing slurry bleeding from the source.

[0045] In step 2) of this invention, the mixing conditions include: a stirring rate of 50-100 rpm and a time of 3-5 min. This ensures uniform distribution of the dry material components, avoids localized gelation or aggregate segregation, and guarantees consistent anti-dispersion and shrinkage properties in every part of the slurry.

[0046] In step 3) of this invention, the mixing conditions include: a stirring rate of 60-120 rpm and a time of 3-5 min. This ensures that the dry mix and bentonite slurry are completely integrated to form a homogeneous basic slurry, free of dry powder and stratification, thus creating conditions for the uniform dispersion of HEMC.

[0047] In step 4) of this invention, to ensure that the HEMC molecular chains are fully extended and uniformly distributed within the slurry, thus constructing a complete three-dimensional fiber cross-linked network and maximizing its anti-dispersion, anti-erosion, and low-shrinkage effects, the dissolution and dispersion conditions include: a stirring rate of 60-120 rpm and a time of 2-3 minutes; HEMC is prone to rapid agglomeration when it encounters dry material pre-absorbs water, making it impossible to completely dissolve and significantly weakening the anti-dispersion effect of the network formation; HEMC is added last, without pre-mixing with the dry material, first forming a homogeneous slurry containing water before addition, which allows for sufficient swelling and dispersion.

[0048] Thirdly, the present invention provides an application of the shield synchronous grouting material as described in the present invention in the synchronous grouting project of the cross-river shield tunnel.

[0049] The shield tunneling synchronous grouting material of this invention is specifically adapted to the complex working conditions of cross-river tunnels, such as high water pressure and crack development, effectively reducing annular grout loss and late-stage seepage defects in the lining; all indicators fully comply with the T / CECS 563-2018 specification, can stably control ground settlement, extend the service life of tunnel lining, and the solid waste resource utilization scheme is in line with the green construction policy of underground engineering, and has the value of wide-ranging promotion and application.

[0050] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto. In the following examples, the drugs and pharmaceuticals are all conventional commercially available products.

[0051] • Material preparation: (1) Cement: PO42.5 ordinary Portland cement, with a specific surface area of ​​355 m². 2 / kg, density 3.06g / cm³ 3 The initial setting time is 233 min, the final setting time is 293 min, the 3-day compressive strength is 26.6 MPa, and the 28-day compressive strength is 50.4 MPa.

[0052] (2) Fly ash: Grade I fly ash, with SiO2 content of 45.10% and Al2O3 content of 36.80%.

[0053] (3) Bentonite: Sodium-based bentonite, whose main component is montmorillonite.

[0054] (4) Fine aggregate: river sand and waste ceramic sand, both with a particle size of 0.1~1mm; Among them, waste ceramic sand is obtained by collecting, washing, drying, crushing, grinding and screening waste ceramics.

[0055] (5) Flocculant: Hydroxyethyl methyl cellulose (HEMC), viscosity 100000 mPa·s, purity greater than 98%.

[0056] Example 1 This embodiment illustrates the preparation of a shield tunnel synchronous grouting material that uses an equal mass of waste ceramic sand to replace 20% of river sand as fine aggregate, and the flocculant dosage is 0.3% of the total mass of cementitious materials (cement and fly ash).

[0057] Table 1 (1) Prepare the raw materials according to the proportions in Table 1; (2) Mix bentonite with water and stir evenly, let stand for 24 hours to allow the bentonite to fully expand and obtain bentonite slurry; (3) Mix cement, fly ash, river sand and waste ceramic sand evenly to obtain dry mix; (4) Add the bentonite slurry from step (1) to the dry mixture from step (2) and stir until uniform; then add HEMC and continue stirring until HEMC is fully dissolved and uniformly dispersed to obtain the shield synchronous grouting material, denoted as B1.

[0058] Example 2 This embodiment illustrates the preparation of shield tunnel synchronous grouting material with a flocculant dosage of 0.4% of the total mass of cementitious materials (cement and fly ash).

[0059] Table 2 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 2, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as B2.

[0060] Example 3 This embodiment illustrates the preparation of a shield tunnel synchronous grouting material with a flocculant dosage of 0.5% of the total mass of cementitious materials (cement and fly ash).

[0061] Table 3 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 3, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as B3.

[0062] Example 4 This embodiment illustrates the preparation of shield tunnel synchronous grouting material with a flocculant dosage of 0.6% of the total mass of cementitious materials (cement and fly ash).

[0063] Table 4 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 4, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as B4.

[0064] Example 5 This embodiment illustrates the preparation of a shield tunneling synchronous grouting material that uses waste ceramic sand of equal mass to replace 30% of river sand as fine aggregate.

[0065] Table 5 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 5, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as B5.

[0066] Example 6 This embodiment illustrates the preparation of a shield tunneling synchronous grouting material that uses waste ceramic sand of equal mass to replace 10% river sand as fine aggregate.

[0067] Table 6 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 6, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as B6.

[0068] Comparative Example 1 This comparative example illustrates the preparation of a shield tunnel synchronous grouting material without the addition of any flocculant.

[0069] Table 7 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 7, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as D1.

[0070] Comparative Example 2 This comparative example illustrates the preparation of a shield tunneling synchronous grouting material using only river sand as fine aggregate.

[0071] Table 8 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 8, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as D2.

[0072] Comparative Example 3 This comparative example illustrates the preparation of shield tunneling synchronous grouting material in which an equal mass of hydroxyethyl cellulose (HEC) replaces HEMC as a flocculant.

[0073] Table 9 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 9, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as D3.

[0074] Comparative Example 4 This comparative example illustrates the preparation of shield tunnel synchronous grouting material with a flocculant dosage of 0.1% of the total mass of cementitious materials (cement and fly ash).

[0075] Table 10 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 10, and other conditions remained unchanged, to obtain the shield tunnel synchronous grouting material, denoted as D4.

[0076] Comparative Example 5 This comparative example illustrates the preparation of shield tunnel synchronous grouting material with a flocculant dosage of 0.2% of the total mass of cementitious materials (cement and fly ash).

[0077] Table 11 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 11, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as D5.

[0078] Comparative Example 6 This comparative example illustrates the preparation of shield tunneling synchronous grouting material using an equal mass of waste ceramic sand to replace 40% of river sand as fine aggregate.

[0079] Table 12 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 12, while other conditions remained unchanged, and the shield tunnel synchronous grouting material was obtained, denoted as D6.

[0080] Comparative Example 7 This comparative example illustrates the preparation of shield tunneling synchronous grouting material (ordinary grout) without the addition of waste ceramic sand and HEMC.

[0081] Table 13 The method of Example 1 was implemented, except that the raw materials were prepared according to the proportions in Table 13, and other conditions remained unchanged, to obtain the shield tunnel synchronous grouting material, denoted as D7.

[0082] Detection Example 1 The physical and mechanical properties of the shield tunnel synchronous grouting materials prepared in Example 1 and Comparative Example 1 were tested. The testing method was in accordance with the "Technical Specification for Application of Synchronous Grouting Materials in Shield Tunneling" (T / CECS 563-2018). The results are shown in Table 14.

[0083] Table 14 As shown in Table 14, all the basic physical and mechanical properties of the shield synchronous grouting materials prepared in Example 1 and Comparative Example 1 meet the limits specified in the "Technical Specification for Application of Synchronous Grouting Materials for Shield Tunneling" (T / CECS 563-2018). Both have the basic feasibility for on-site shield tunneling construction. However, the shield synchronous grouting material prepared in Example 1 with a dosage of 0.3% HEMC has significantly better comprehensive working performance and water retention stability than the shield synchronous grouting material prepared in Comparative Example 1 without any flocculant.

[0084] Compared with the shield synchronous grouting material prepared in Comparative Example 1, the shield synchronous grouting material prepared in Example 1 of this invention has a slightly reduced fluidity but still meets the pumping standard, and the consistency is optimized to the optimal range of the specification; the bleeding rate is reduced by 62%, and the water retention and anti-segregation ability is significantly improved; the setting time is extended to 14 hours, providing sufficient construction operation window; due to the slight air entrainment effect of HEMC, the compressive strength of the shield synchronous grouting material prepared in Example 1 is slightly reduced in water, but still has sufficient performance margin, making it more suitable for water-rich and dynamic shield tunneling scenarios.

[0085] It is evident that the addition of HEMC significantly optimizes the water retention and homogeneity of the grout without compromising the basic construction performance of the grouting material or exceeding the specified threshold, making it more suitable for the special working conditions of cross-river tunnels with abundant and flowing water. In contrast, the shield synchronous grouting material prepared without any flocculant in Comparative Example 1 is only suitable for waterless and still water conventional strata, and its underwater service performance has obvious shortcomings.

[0086] Detection Example 2 The anti-water dispersion properties of the shield tunneling synchronous grouting materials prepared in Examples 1-4, Comparative Example 1, and Comparative Example 3-5 were tested, and the results were as follows: Figures 1-2 .

[0087] The water dispersion test data of the shield synchronous grouting materials prepared in Example 1, Comparative Example 1 and Comparative Example 3 are shown in Table 15.

[0088] Table 15 As shown in Table 15, compared with the shield synchronous grouting material prepared in Comparative Example 1, the shield synchronous grouting material prepared in Example 1 has a significantly improved water dispersion resistance performance in all aspects. At the same time, compared with the HEC system with the same dosage (Comparative Example 3), HEMC has a better underwater stability effect and is perfectly suited to the high water pressure dynamic water environment of cross-river tunnels.

[0089] The turbidity of the shield tunneling synchronous grouting material prepared in Comparative Example 1 was 465.6 NTU, while the turbidity of the shield tunneling synchronous grouting material prepared in Example 1 was 77.5 NTU, representing an overall reduction of 83.4%. This indicates that HEMC can effectively bind solid particles such as cement and aggregates, significantly reducing their loss during water immersion. The pH of the shield tunneling synchronous grouting material prepared in Comparative Example 1 was 11.16, indicating strong alkalinity, while the pH of the shield tunneling synchronous grouting material prepared in Example 1 was 8.81, indicating near-neutral pH, further reducing... The alkaline leachates reduce corrosion and pollution of surrounding water bodies and surrounding rocks, thus improving the green and environmentally friendly properties. The 3-day water-to-land strength ratio of the shield tunneling synchronous grouting material prepared in Comparative Example 1 was 0.67, while that of the shield tunneling synchronous grouting material prepared in Example 1 was 0.89, representing an increase of 32.8%. The 28-day water-to-land strength ratio of the shield tunneling synchronous grouting material prepared in Comparative Example 1 was 0.63, while that of the shield tunneling synchronous grouting material prepared in Example 1 was 0.88, representing an increase of 39.7%. The significantly improved water-to-land strength ratio indicates extremely low strength decay of the grout after hardening in water, ensuring long-term stable filling and support behind the lining. Further comparison with the shield tunneling synchronous grouting material of Comparative Example 3, which used an equal amount of 0.3% HEC instead of HEMC, resulted in a turbidity of 183.8 NTU, a pH of 9.53, and water-to-land strength ratios of 0.83 and 0.81 after 3 and 28 days, respectively. In contrast, the shield tunneling grouting material of Example 1 exhibited lower turbidity, a pH closer to neutral, and a higher water-to-land strength ratio at all ages compared to Comparative Example 3. This indicates that, at the same dosage, HEMC demonstrates superior flocculation and locking efficiency for grout particles compared to HEC, making it more suitable for meeting the stringent requirements of underwater stability and strength retention in grouting materials under high water pressure and dynamic water conditions. In summary, the data in Table 15 fully validate that the HEMC selected in this invention, at an appropriate dosage, imparts excellent anti-water dispersion properties and underwater strength retention to the grouting material.

[0090] Combination Figure 1 The experimental results corroborate that, under the same dosage conditions, the supernatant of the shield tunnel synchronous grouting material prepared with 0.3% HEC in Comparative Example 3 was significantly more turbid than that of the shield tunnel synchronous grouting material prepared with 0.3% HEMC in Example 1. The quantitative indicators such as turbidity and water-land strength ratio were also inferior to those of the shield tunnel synchronous grouting material prepared in Example 1, proving that the efficiency of flocculation and locking of particles under low HEMC dosage is far superior to that of traditional HEC.

[0091] Depend on Figure 2It is evident that the shield tunnel synchronous grouting materials prepared with 0.1% HEMC in Comparative Example 4 and 0.2% HEMC in Comparative Example 5 showed significant turbidity in the upper water and severe sedimentation and stratification at the bottom after the grouts were left to stand. This indicates that HEMC at a dosage of 0.1-0.2% cannot form a complete and continuous three-dimensional fiber cross-linking network in the grout, resulting in insufficient encapsulation and locking ability for cement and aggregate particles. Upon contact with water, a large amount of solid particles dissolve and disperse, and the anti-water dispersion effect is substandard.

[0092] The shield tunneling synchronous grouting material prepared with 0.4% HEMC in Example 2, the shield tunneling synchronous grouting material prepared with 0.5% HEMC in Example 3, and the shield tunneling synchronous grouting material prepared with 0.6% HEMC in Example 4 showed very little difference in water clarification compared to the shield tunneling synchronous grouting material prepared in Example 1. The improvement in the water dispersion resistance of the grout tended to saturate, indicating that further increasing the amount of HEMC could not significantly improve underwater stability.

[0093] From the perspective of balancing overall performance and cost, the optimal dosage of HEMC is 0.3%. If the dosage of HEMC is continuously increased beyond 0.3%, it will not only fail to improve the anti-dispersion effect, but will also cause a significant decrease in slurry fluidity and deterioration in pumping performance, while significantly increasing the cost of raw materials, thus having no practical engineering value.

[0094] In summary, there is a critical threshold of 0.3% for HEMC content. Below this value, the anti-water dispersion performance is insufficient, while above this value, the performance benefits are saturated. This confirms the rationality of selecting 0.3% HEMC by total mass of cementitious materials as the optimal content in this invention.

[0095] Detection Example 3 The anti-dynamic water erosion performance of the shield synchronous grouting materials prepared in Example 1, Comparative Example 1 and Comparative Example 3 was tested, and the results are shown in Table 16.

[0096] Table 16 As shown in Table 16, the retention rate of the shield tunnel synchronous grouting material prepared with 0.3% HEMC in Example 1 was significantly higher than that of the shield tunnel synchronous grouting material prepared without any flocculant in Comparative Example 1 at all flow velocities. The higher the water flow velocity, the more significant the gain of HEMC in improving the retention rate, with a 27.5% increase in retention rate at a high flow velocity of 0.3 m / s. Under the same dosage, the shield tunnel synchronous grouting material prepared with 0.3% HEMC in Example 1 showed better resistance to dynamic water erosion than the shield tunnel synchronous grouting material prepared with 0.3% HEC in Comparative Example 3, effectively solving the engineering problems of dynamic water erosion of grout and incomplete filling in cross-river tunnels.

[0097] Detection Example 4 The grout volume shrinkage and permeability loss rates of the shield tunneling synchronous grouting material prepared in Example 1 and the shield tunneling synchronous grouting material prepared in Comparative Example 7 were tested. The results are shown in Table 17 and 18. Figures 3-4 .

[0098] Table 17 As shown in Table 17, the shield tunneling synchronous grouting material prepared with 0.3% HEMC in Example 1 exhibits significantly lower shrinkage in free shrinkage, volume shrinkage in intact sandstone, intact mudstone, fractured sandstone, and fractured mudstone formations compared to the shield tunneling synchronous grouting material prepared in Comparative Example 7. The shrinkage reduction in fractured rock mass exceeds 60%, demonstrating outstanding advantages in low shrinkage and impermeability.

[0099] Depend on Figure 3 , Figure 4 As can be seen from the infiltration and loss curves, under the conditions of intact sandstone, intact mudstone, fractured sandstone, and fractured mudstone, the shield synchronous grouting material prepared in Comparative Example 7 has a fast infiltration and loss rate and a high final loss rate; the shield synchronous grouting material prepared in Example 1 with a dosage of 0.3% HEMC has a slow growth in slurry seepage and a significantly lower steady-state loss rate, proving that the HEMC and ceramic sand compound system in the shield synchronous grouting material of the present invention can effectively block the seepage and loss of slurry along rock fractures, and is suitable for high water pressure fractured cross-river shield construction.

[0100] Case 5 The microstructure of the hardened shield tunneling synchronous grouting material prepared in Example 1 and Comparative Example 1 was observed using scanning electron microscopy (SEM). The results are shown in the figure. Figure 5 As shown.

[0101] Depend on Figure 5 The SEM microstructure of the hardened grout revealed significant differences in the internal microstructure between the shield tunneling synchronous grouting material prepared in Comparative Example 1 without any flocculant and the shield tunneling synchronous grouting material prepared in Example 1 with 0.3% HEMC. This difference can be explained at the microscopic level as a mechanism for the difference in macroscopic performance. Figure 5 In the middle (a), the shield synchronous grouting material sample prepared without any flocculant in Comparative Example 1 is shown. The internal structure of the grout is loose, the interface between fly ash particles and cement hydration product CSH gel is clear, there is a lack of continuous overlapping structure, there are many pores and weak interfacial bonding; when exposed to flowing water, the particles are easily peeled off and dispersed, and the shrinkage is large and the impermeability is poor.

[0102] Figure 5(b) shows a shield tunneling synchronous grouting material sample prepared with 0.3% HEMC in Example 1 of this invention. A large number of fibrous flocculent HEMC cross-linked aggregates are generated within the grout, distributed in a network pattern between cement paste, fly ash particles, and CSH gel, forming a continuous three-dimensional skeleton. The polymer fibers bridge and encapsulate the inorganic hydration products and aggregate particles, filling internal pores and significantly improving overall density and interparticle bonding. This fibrous network structure is the core internal factor contributing to the grout's resistance to water dispersion, erosion by flowing water, and low shrinkage. The network structure can lock in internal free water, reducing volume shrinkage caused by water evaporation and fissure seepage; simultaneously, it strengthens interparticle cohesion, resists water erosion and dilution, and significantly reduces the rate of underwater strength attenuation.

[0103] Case 6 The elemental composition of the hardened shield tunneling synchronous grouting material prepared in Example 1 and Comparative Example 1 was analyzed using X-ray energy dispersive spectroscopy (EDS). The results are as follows: Figure 6 As shown.

[0104] Depend on Figure 6 The EDS energy dispersive spectroscopy analysis results of the hardened slurry show that the elemental composition of the shield synchronous grouting material prepared without any flocculant in Comparative Example 1 is significantly different from that of the shield synchronous grouting material prepared with 0.3% HEMC in Example 1, which directly confirms that the HEMC organic components are uniformly distributed inside the hardened slurry.

[0105] Figure 6 In the middle (a), the shield synchronous grouting material sample prepared without any flocculant in Comparative Example 1 has a low intensity of the characteristic peak of C element in the energy spectrum and a content of only 13.86%. The grout is mainly composed of inorganic hydration product elements O, Si and Ca, with no large amount of organic components filling the pores. Figure 6 (b) shows a shield tunneling synchronous grouting material sample prepared with 0.3% HEMC in Example 1. The peak value of carbon in the energy spectrum is significantly increased, with the atomic percentage rising to 29.87%, indicating that the long-chain organic molecules of HEMC are uniformly dispersed and retained at the interface between cement paste pores and aggregates. The elemental distribution mechanism confirms that the high proportion of carbon corresponds to the fibrous network structure of HEMC. The organic components are interspersed between CSH gel and fly ash particles, forming an organic-inorganic composite interface. This interface not only locks in free water within the grout but also enhances the cohesion of solid particles through molecular bridging. Figure 5 The fiber flocculent cross-linking morphology observed by SEM corroborates each other, further demonstrating that HEMC is not merely floating on the surface of the slurry, but rather fully penetrates into the microporous system of the hardened slurry, stably constructing a three-dimensional constraint network. This is the fundamental microscopic basis for improving the slurry's resistance to water dispersion, low shrinkage, and resistance to dynamic water erosion.

[0106] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0107] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0108] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A shield tunneling synchronous grouting material based on waste ceramic sand, characterized in that, The shield tunneling synchronous grouting material comprises cementitious materials, fine aggregates, bentonite, water, and flocculants; wherein... The cementitious material includes cement and fly ash; The fine aggregate is composed of river sand and waste ceramic sand, with the waste ceramic sand accounting for 10-30% of the total mass of the fine aggregate. The flocculant is hydroxyethyl methyl cellulose, and the amount of hydroxyethyl methyl cellulose is 0.25~0.6% of the total mass of the cementitious material.

2. The shield tunneling synchronous grouting material according to claim 1, characterized in that, The cement is PO42.5 ordinary Portland cement with a specific surface area of ​​350~360m². 2 / kg, density 3~3.1g / cm³ 3 Initial setting time 220~250min, final setting time 280~300min, 3d compressive strength 24~30MPa, 28d compressive strength 48~52MPa; The fly ash is Class I fly ash, with a SiO2 content of 44-46% and an Al2O3 content of 35-38%. The bentonite is sodium-based bentonite.

3. The shield tunneling synchronous grouting material according to claim 1 or 2, characterized in that, The particle size of the river sand is 0.1~1mm; The particle size of the waste ceramic sand is 0.1~1mm.

4. The shield tunneling synchronous grouting material according to any one of claims 1-3, characterized in that, The hydroxyethyl methyl cellulose has a viscosity of 80,000~120,000 mPa·s and a purity of ≥98%.

5. The shield tunneling synchronous grouting material according to any one of claims 1-4, characterized in that, The shield tunneling synchronous grouting material, by weight, consists of the following components: 500-600 parts cementitious material, 640-680 parts fine aggregate, 50-60 parts bentonite, 330-360 parts water, and 1.25-3.6 parts flocculant.

6. A method for preparing a shield tunneling synchronous grouting material as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: 1) Mix bentonite with water and let it stand to expand, thus obtaining bentonite slurry; 2) Mix cement, fly ash, river sand, and waste ceramic sand to obtain a dry mix; 3) Add the bentonite slurry from step 1) to the dry mix from step 2) and mix. 4) Add hydroxyethyl methyl cellulose, dissolve and disperse to obtain the shield tunnel synchronous grouting material.

7. The preparation method according to claim 6, characterized in that, In step 1), the mixing conditions include: a stirring speed of 40-80 rpm and a time of 2-3 min; The static puffing time is 12~36h.

8. The preparation method according to claim 6, characterized in that, In step 2), the mixing conditions include: a stirring rate of 50-100 rpm and a time of 3-5 min.

9. The preparation method according to claim 6, characterized in that, In step 3), the mixing conditions include: a stirring speed of 60~120 rpm and a time of 3~5 min; In step 4), the conditions for dissolution and dispersion include: a stirring rate of 60-120 rpm and a time of 2-3 min.

10. The application of a shield tunnel synchronous grouting material as described in any one of claims 1-5 in synchronous grouting projects for cross-river shield tunnels.